Divergent roles of m6A in orchestrating brown and white adipocyte transcriptomes and systemic metabolism - Ling Xiao; Dario F. De Jesus; Cheng-Wei Ju; Jiang-Bo Wei; Jiang Hu; Ava DiStefano-Forti; Valeria Salerno Gonzales; Tadataka Tsuji; Siying Wei; Matthias Blüher; Yu-Hua Tseng; Chuan He; et al. (Nature Communications)
Abstract N6-methyladenosine (m6A) is among the most abundant mRNA modifications, yet its cell-type-specific regulatory roles remain unclear. Here we show that m6A methyltransferase-like 14 (METTL14) differentially regulates transcriptome in brown versus white adipose tissue (BAT and WAT), leading to divergent metabolic outcomes. In humans and mice with insulin resistance, METTL14 expression differs significantly from BAT and WAT in the context of its correlation with insulin sensitivity. Mettl14-knockout in BAT promotes prostaglandin secretion, improving systemic insulin sensitivity. Conversely, Mettl14-knockout in WAT triggers adipocyte apoptosis and systemic insulin resistance. m6A-seq and RNA-seq integration revealed upregulated prostaglandin biosynthesis pathways in BAT and apoptotic pathways in WAT with Mettl14 deficiency. Stable METTL14-knockout hBAs/hWAs show METTL14-mediated m6A promotes mRNA decay of PTGES2 and CBR1 in hBAs and TRAIL and TNFR1 in hWAs. These data shed light on the ability of m6A to impact metabolism in a cell-type-specific manner with implications for influencing the pathophysiology of metabolic diseases.